Exploring Potential Impact‐Induced Magnetic Signatures at the Tunguska Event Epicenter Using UAV‐Based Magnetometry - M. Takáč; G. Kletetschka; N. Hasson; R. Kavkova; V. Petrucha (Earth and Space Science)
Abstract The Tunguska event of 1908 remains the most significant atmospheric explosion in recorded history, yet its geophysical effects, particularly its impact on Earth's magnetic field, remain uncertain. This study presents the first detailed magnetometer survey of the Tunguska epicenter, aiming to map regional magnetic anomalies and assess potential impact‐induced magnetization. The survey used unmanned aerial vehicle and covered approximately 30 square kilometers, revealing a complex pattern of magnetic anomalies that correlate with known geological structures. Notably, some anomalies exhibit spatial alignment with the presumed trajectory of the airburst (∼300° azimuth), suggesting potential influence from the event. This spatial correlation raises the possibility that transient electromagnetic effects from the airburst, such as ionization‐induced remagnetization or shock‐induced changes in magnetic mineralogy, could have contributed to the observed anomaly distribution. However, due to the limitations of our data set, we cannot definitively attribute any observed anomalies to impact‐related remagnetization. Our analysis identifies regions where future rock magnetic studies could provide further insights. We discuss possible mechanisms for transient remagnetization, including ionization effects and shock‐induced mineral transformations, while emphasizing the necessity of future paleomagnetic sampling to test these hypotheses. These findings establish a foundational geophysical data set for future interdisciplinary investigations into the Tunguska event's environmental and geological consequences.